Identifying engagement strategies for Hispanic youth with anxiety: A youth-centered, Design-Thinking approach. - Thea Runyan; Kristen Hassmiller Lich; Karl Umble; Karen Li; Kiersten Daniel Baca; Leah Frerichs (PLoS ONE)
Anxiety is the most common and widespread mental health disorder impacting youth between the ages of 10-19. Youth of color including Hispanic youth are disproportionately impacted. Fewer than 20% of youth of color who need mental health services are receiving them. However, we know relatively little about how to best engage Hispanic youth to increase their use of mental health services. The aims of this study were to better understand the personal, environmental, and behavioral factors that impact Hispanic adolescents help-seeking behaviors and to identify the important criteria needed to develop an appealing intervention that would increase engagement with mental health services. This study used a Design Thinking process-a participatory research approach that included qualitative and engaged methods. In-depth interviews (n = 8) and a Design Thinking workshop (n = 11 participants) were conducted with Hispanic youth with anxiety residing in the San Francisco Bay Area. In-depth interviews were coded using Social Cognitive Theory to identify key themes that impact an adolescent's decision to seek help. The 90-minute workshop included ideation and Design Thinking activities including personas, mind-mapping, and analytical problem-solving to identify the most important tools and strategies that could be used to manage anxiety. The study identified several themes that directly impact program design, including barriers to seeking help for anxiety, coping strategies, sources of support, and specific program ideas. The findings revealed that Hispanic youth want a culturally relevant technology-based program that provides easily accessible educational information and coping strategies delivered in an engaging format that also facilitates mental health support with a trusted adult. The results reinforce the need to develop culturally inclusive and innovative programs designed specifically for priority populations to increase youth engagement with mental health services.